Evolution of patients operated for gastric cancer - Castiglioni, Dinorah (Cirugía del Uruguay, 2020)
A survey is carried out of 200 cases of gastric cancer comprising 167 operations: 52 simple laparatomies, 47 palliative interventions and 68 resections (of which 14 palliative)